Konsep Integrasi Pembangkit Berbasis Energi Terbarukan Sebagai Sistem Mikrogrid Di Kabupaten Pesisir Selatan - Rauf, Rosnita (JURNAL NASIONAL TEKNIK ELEKTRO, 2013)
Energy grid management systems are the future of many developed countries today was developed called smart grid. Energy management in a smart grid is to use the concept of merging a few plants and a group of users in a particular area or within a certain grid. Generating an initial variable as the giver of energy input while the end users are variable power grid as a user of this hybrid energi. Sistem simulated using HOMER program and perform calculations with MATLAB system. Integration of these variables in a management area network will provide the optimal parameter if it can be supported by computer networks to obtain communications data from the SCADA system. With mikrogrid designed to have two streams, namely electricity and information flow,  SCADA here designed to cover all the flow of  information from the plant to the customer. The basic activity is the activity under taken monitoring and control of activities which aim to balance the grid. Monitoring aims to add to the data on plants and customers in order to assist decision-making at the micro grid system  inside. Control activities aim to maintain a balanced energy intake of multiple power plant priority points toward energy use by multiple end users in the grid.Keywords: Energy, Mikrogrid, HOMER, MATLAB, SCADA AbstrakSistem pengelolaan grid energi masa depan yang banyak dikembangkan negara maju saat ini biasa disebut smart grid. Pengelolaan energi dalam smart grid ini menggunakan konsep penggabungan beberapa pembangkit dan  sekelompok  pengguna  dalam  wilayah  tertentu  atau  dalam  grid tertentu.  Pembangkit merupakan  variabel awal  sebagai  pemberi masukan  energi  sedangkan  pengguna  merupakan  variabel  akhir  grid sebagai  pemakai energi. Sistem tenaga hybrid ini disimulasikan dengan menggunakan program HOMER dan melakukan perhitungan system dengan MATLAB.  Penggabungan  variabel-variabel  tersebut  dalam sebuah  area  network  akan memberikan  pengelolaan parameter yang optimal jika dapat didukung dengan jaringan computer untuk mendapatkan komunikasi data dari system SCADA. Dengan mikrogrid dirancang mempunyai dua  aliran  yaitu  aliran  listrik  dan  aliran informasi,  SCADA  disini dirancang  untuk  mencakup semua aliran informasi dari pembangkit hingga pelanggan. Aktivitas dasar yang dilakukan adalah aktivitas monitoring dan aktivitas  kendali  yang bertujuan  untuk  keseimbangan  grid.  Monitoring  bertujuan  untuk menambah data pada pembangkit dan pelanggan sehingga dapat membantu pengambilan keputusan pada mikro system didalam grid. Aktivitas  pengendalian  bertujuan  untuk  menjaga  pengasupan  energi yang  seimbang  dari multiple power plant menuju titik-titik prioritas penggunaan energi oleh multiple end user didalam grid. Keywords: Energy, Mikrogrid, HOMER, MATLAB, SCADA